Persepsi Orang Tua Tentang Kerentanan Dan Keseriusan Penyakit Terhadap Kekambuhan Ispa Pada Balita Di Puskesmas X Sumba Barat - Woli, Onceniati S; Putri, Ronasari Mahaji; Devi, Hilda Mazarina (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
ISPA in toddlers is an infectious disease of the first order of the ten most common diseases at Puskesmas X, West Sumba, and recurrences often occur, the recurrence rate is associated with parents' poor perception of ISPA. The study aimed to analyze the relationship between parents' perceptions of the vulnerability and seriousness of the disease to the recurrence of ISPA in toddlers at Puskesmas X, West Sumba. Cross-sectional study design used, with a population of 105 parents of toddlers with ISPA, a sample of 81 participant selected using purposive sampling. The research instrument was medical record data for ISPA recurrence as well as questionnaires on perceptions of vulnerability and seriousness that had been tested for validity (r count 0.514) and reliability for perceived vulnerability (α=925), and perceived seriousness (α=0786). The results showed that almost half of the parents had perceived susceptibility in the sufficient category (36%) and perceived seriousness in the sufficient category (48%) and more than half of the toddlers experienced relapse (75%). Chi-square test results on parents' perceptions of vulnerability (p-value 0.003); Fisher's exact test (p-value 0.000) revealed that there was a relationship between parents' perceptions of the susceptibility and seriousness of the disease to the recurrence of ISPA in toddlers at Puskesmas X, West Sumba.